Inside Back Cover: Vitamin B12 Catalysis: Probing the Structure/Efficacy Relationship (Chem. Eur. J. 29/2017). Issue 29 (30th March 2017) - Karczewski, Maksymilian; Ociepa, Michał; Pluta, Katarzyna; ó Proinsias, Keith; Gryko, Dorota
Abstract : The influence of peripheral groups present at the macrocycle ( c‐, d‐, meso‐ positions) of vitamin B12 derivatives on catalytic activity in the C−H activation of olefins is described. These catalysts are shown to halo the engraved bell. To justify the obtained yields, DFT calculations were performed, examining the relationship between the electron density on the cobalt ion and the yield. We discovered that the experimental points mapped out the bell‐shaped Gaussian distribution. More information can be found in the Full Paper by K. ó Proinsias, D. Gryko et al. onpage 7024 .